The crucial role of emilin 1 gene expression during progression of tumor growth - Rabajdova, Miroslava; Urban, Peter; Spakova, Ivana; Saksun, Ladislav; Dudic, Rastislav; Ostro, Alexander; Caprnda, Martin; Kruzliak, Peter; Adamek, Mariusz; Marekova, Maria (Journal of cancer research and clinical oncology, 2016)
BACKGROUND: This study describes the effect of rapid tumor growth of patients suffering from various grades of malignant ductal breast carcinoma associated with the gene expression of ECM protein emilin 1, in correlation with the number of gene copies of emilin 1 and degradation of tumor tissue proteins. METHODS: A total of 40 examined patients participated in the experiment (controls, n = 10, grades GI-GIII, each n = 10). After isolation of total mRNA, transcription of mRNA into the cDNA was performed. Quantification of gene expression changes was detected by the real-time PCR method. Analysis at the protein level was performed via Western blot method. RESULTS: During the detection of changes at the mRNA level, a significantly decreased level of emilin 1 in tumor tissues with grade II (about 54 ± 8 % lower than control) was identified. Protein-level analysis indicated an increased level of emilin 1 in tumors with grade I in comparison with control samples (about 10 ± 3 %). CONCLUSION: Obtained results demonstrated that the suppressive role of emilin 1 is related to the grade of growing breast tumors, and associated with increased hypoxia in the tumor microenvironment followed by elevated unfolding and degradation of tissue proteins.
Keywords: nádory prsu; Female; Blotting, Western; ženské pohlaví; Gene Dosage; Membrane Glycoproteins; lidé; Carcinoma, Ductal, Breast; Neoplasm Grading; Breast Neoplasms; messenger RNA; studie případů a kontrol; komplementární DNA; RNA, Messenger; western blotting; stupeň nádoru; Case-Control Studies; exprese genu; membránové glykoproteiny; duktální karcinom prsu; DNA, Complementary; genová dávka; kvantitativní polymerázová řetězová reakce; Gene Expression; Real-Time Polymerase Chain Reaction; Humans